The Optimization of Design and Energy Consumption for Helical Gear Pumps by Benchmarking - Burak Öztürk; İrem Duzdar Argun; Barış Kantoğlu (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2018)
The various types of helical gear pumps can be produced to transfer thegasoline, diesel, chemicals, and oil. Helical gear pumps are used by motorpower in fuel selling and transfer points, and by gear shafts at mobiletransfer trucks. These pumps are classified in three main groups as internal gear,pallet, and helical pumps. The common feature of them is sucking the liquidfrom the container placed under ground level and transferring it to the highlevels. The lower flow rates, noisy working, and the quick corrosion of gearwhen the pump is running closing outlet valve are the disadvantages of thesepumps produced in our country. The aim of this study is to design a newgeneration of helical gear pump which will eliminate or at least decrease thesedisadvantages. It is expected to minimize energy consumption, and to protectthe corrosion of gears coming from the high pressure at this new design. Thedimensions of this pump will be appropriated to the chassis of the truck and atminimum weight. The various types of helical gear pumps, both domestic production and imported, areevaluated in a study performed with the R amp;D department of the petroleumindustrialist firm IPT (Ismet Pump Technology) on their energy consumptions,flow rates, dimensions, weights, and maximum pressure criteria. The reasons ofthe noiseless working and the high flow rates are explored at the end of thisbenchmarking analysis. Through the benchmarking, by-pass system, liquidclearance between the gears, and the faults at the inlet and outlet design ofthe domestic products are identified and a new design is proposed. In the newdesigned pump the number of teeth is decreased and the cavitation of the inletand outlet is minimized. Besides these the transfer capacity of the pump isincreased from 400 l/min to 600 l/min. The energy requirement for 1 liter ofliquid is compared with the other products to measure its energy efficiency.The result is also positive at this point of view. Then, this new design isprotected by patent registration.